Mathematical modeling of a solid oxide fuel cell operating on biogas - Wandercleiton Cardoso; Renzo di Felice; Raphael Colombo Baptista (Institute of Advanced Engineering and Science, 2021)
Solid oxide fuel cells (SOFC) are the most efficient devices for directly converting the chemical energy of a fuel into electrical energy. This is one of the main reasons why these fuel cells have received a lot of attention from the scientific community and from several developers who have invested in the use of this technology in various applications. Biogas is one of the products of anaerobic decomposition (absence of gaseous oxygen) of organic matter, which occurs due to the action of certain types of bacteria. Biogas is mainly composed of methane (CH4) and carbon dioxide (CO2) and its use in solid oxide fuel cells has been investigated since Biogas is a renewable biofuel. The aim of this paper was to perform mathematical modeling of a solid oxide fuel cell operating on biogas. The results confirmed that the overall efficiency of the system is above 94% and the largest irreversibilities of the system are related to heat exchangers.